2009
DOI: 10.1111/j.1473-2165.2009.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides: signaling the future

Abstract: SummaryNatural processes within the body are modulated almost exclusively by the interaction of specific amino acid sequences, either as peptides or as subsections of proteins. With respect to skin, proteins and peptides are involved in the modulation of cell proliferation, cell migration, inflammation, angiogenesis, melanogenesis, and protein synthesis and regulation. The creation of therapeutic or bioactive peptide analogs of specific interactive sequences has opened the door to a diverse new field of pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 32 publications
1
59
0
2
Order By: Relevance
“…On the other hand, natural bioactive peptides have gained more attention in cosmetics industry rather than drug making, which is justifiable since cosmetics are consumed topically and therefore, toxicity of natural peptides in systemic applications is a minor concern when it comes to the production of natural-peptide-based cosmetics. Bioactive peptides have been specifically emphasized in skincare and cosmetic dermatology because of their ability to stimulate collagen and render botox-like antiwrinkle effect (Fields et al, 2009).…”
Section: Commercial Applications Of Bioactive Peptides and Hydrolysatesmentioning
confidence: 99%
“…On the other hand, natural bioactive peptides have gained more attention in cosmetics industry rather than drug making, which is justifiable since cosmetics are consumed topically and therefore, toxicity of natural peptides in systemic applications is a minor concern when it comes to the production of natural-peptide-based cosmetics. Bioactive peptides have been specifically emphasized in skincare and cosmetic dermatology because of their ability to stimulate collagen and render botox-like antiwrinkle effect (Fields et al, 2009).…”
Section: Commercial Applications Of Bioactive Peptides and Hydrolysatesmentioning
confidence: 99%
“…Hexapeptide-14 (palmitoyl hexapeptide-14) has been reported to stimulate cell migration, collagen synthesis, and fibroblast proliferation and scaffolding [1]. A 12-week study with 29 volunteers showed results of reduced fine lines and wrinkles by palmitoyl hexapeptide-14.…”
Section: Hexapeptide-14mentioning
confidence: 99%
“…The name peptide is coming from pepton [peptos: digested (Greek)]. Naturally occurring human peptides are known for cellular communication, such as protein regulation, cell proliferation, cell migration, inflammation, angiogenesis, and melanogenesis [1], which results in a broad variety of physiological processes including defense, immunity, stress, growth, homeostasis, and reproduction [2]. The first peptides were described by Emil Fischer and Hofmeister in the early 19th century.…”
Section: Introductionmentioning
confidence: 99%
“…적 효과로 인해 고기능성 물질로 인식되고 있다 [5]. 피부 미용 소재로써 BAP의 기능 중 cellular messenger에 관한 연구는 가장 최근이며 [6] 2009년 미국의 경우 스킨케어 성분으로 시장에서 확인된 피부 미용 소재 BAP는 25여 종으로 파악되 었고 [4] 주요 기능은 진피층 콜라겐 합성에 관련된 것이었 다 [5].…”
unclassified
“…피부 미용 소재로써 BAP의 기능 중 cellular messenger에 관한 연구는 가장 최근이며 [6] 2009년 미국의 경우 스킨케어 성분으로 시장에서 확인된 피부 미용 소재 BAP는 25여 종으로 파악되 었고 [4] 주요 기능은 진피층 콜라겐 합성에 관련된 것이었 다 [5]. Caffeoyl tripeptide-1 (CT-1), digalloyl tetrapeptide-19 (DT-19), nicotinoyl tripeptide-1 (NT-1)은 Fmoc 기반의 고체 상 펩타이드 합성법 (solid phase peptide synthesis; SPPS) 을 이용하여 최근에 개발된 새로운 BAP이다.…”
unclassified